PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE I AM THE UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERPEN SISWA MAS - Lili Yanti; Christanto Syam; Laurensius Salem (Universitas Tanjungpura, 2017)
AbstractThe purpose of this research is to describe the implementation and evaluation of active learning strategy type i am the learning skill of writing short story in grade X student A MAS Yasti Singkawang. The method of this research is qualitative research design method of action class that includes 3 cycles. The results showed that students short story writing skills can be improved by the application of active learning strategy type i am the evidenced by the value of the process and the value of writing short stories. In the first cycle shows that the process of writing short story writing is included in the good category while the result of writing short story students reaches 33%. In the second cycle of learning process of writing short story included in good category while the result of writing short story of student reach 57%. In the third cycle of learning process of writing short story included in the good category while the result of writing short story students reach 90% and has reached and exceeded the classical that is determined that is 75%. Keywords: Active Learning Strategy Type I Am The, Writing Skills, short stories